ENUMERATION OF POTENTIAL FUNGI ON POST-MINING LAND OF PT. VALE INDONESIA Tbk SOROWAKO - Larekeng, Siti Halima; Nursaputra, Munajat; Nasri; Hamzah, Andi Siady; Jufri, Sri Wahyuni; Akzad, Muhammad Bima; Ardiansyah, Andri (Jurnal Galung Tropika, 2024)
This study investigated the diversity and density of rhizosphere fungi in the post-nickel mining land of PT. Vale Indonesia Tbk., to assess its potential in supporting revegetation and ecological recovery. By analyzing fungal populations at various dilution levels in PDA media, this study revealed the relationship between post-reclamation duration and increased soil microbiological activity. The results showed that longer reclaimed land had denser fungal populations, especially at lower dilutions, indicating the importance of rhizosphere fungi in soil health recovery. This study confirmed that the presence of plants significantly affected the abundance and diversity of rhizosphere fungi. These findings provide insight into the importance of selecting specific fungal species for post-mining land revegetation strategies, which support plant growth and accelerate ecological recovery. It can contribute to developing best practices in ecological engineering and environmental management in post-mining areas.